Midnight in europe ebook A novel. - Furst, Alan (Night Soldiers, 2014)
NEW YORK TIMES BESTSELLER Paris, 1938. As the shadow of war darkens Europe, democratic forces on the Continent struggle against fascism and communism, while in Spain the war has already begun. Alan Furst, whom Vince Flynn has called “the most talented espionage novelist of our generation,” now gives us a taut, suspenseful, romantic, and richly rendered novel of spies and secret operatives in Paris and New York, in Warsaw and Odessa, on the eve of World War II.   Cristián Ferrar, a brilliant and handsome Spanish émigré, is a lawyer in the Paris office of a prestigious international law firm. Ferrar is approached by the embassy of the Spanish Republic and asked to help a clandestine agency trying desperately to supply weapons to the Republic’s beleaguered army—an effort that puts his life at risk in the battle against fascism.   Joining Ferrar in this mission is a group of unlikely men and women: idealists and gangsters, arms traders and aristocrats and spies. From shady Paris nightclubs to white-shoe New York law firms, from brothels in Istanbul to the dockyards of Poland, Ferrar and his allies battle the secret agents of Hitler and Franco. And what allies they are: there’s Max de Lyon, a former arms merchant now hunted by the Gestapo; the Marquesa Maria Cristina, a beautiful aristocrat with a taste for danger; and the Macedonian Stavros, who grew up “fighting Bulgarian bandits. After that, being a gangster was easy.” Then there is Eileen Moore, the American woman Ferrar could never forget.   In Midnight in Europe, Alan Furst paints a spellbinding portrait of a continent marching into a nightmare—and the heroes and heroines who fought back against the darkness. Praise for Alan Furst and  Midnight in Europe   “Furst never stops astounding me.” —Tom Hanks   “Furst is the best in the business.” —Vince Flynn   “Elegant, gripping . . . [Furst] remains at the top of his game.” —The New York Times   “Suspenseful and sophisticated . . . No espionage author, it seems, is better at summoning the shifting moods and emotional atmosphere of Europe before the start of World War II than Alan Furst.” —The Wall Street Journal   “Endlessly compelling . . . Furst delivers an observant, sexy, and thrilling tale set in the outskirts of World War II. In Furst’s hands, Paris once again comes alive with intrigue.” —Erik Larson   “Too much fun to put down . . . [Furst is] a master of the atmospheric thriller.” —The Boston Globe